Home based physical exercise for prevention and management of COVID-19 pandemic and for its associated consequences - Teferi, G. (American Journal of Sports Science and Medicine, 2020)
Corona viruses are sort of viruses that are phenotypically and genotypically diverse. The outbreak of COVID-19 starts in December 2019 in Wuhan, China. The research method of this article is a systematic review based on search strategy by used terms in relation with physical activity and Covid-19. The COVID-19 pandemic has forced many people around the world to stay at home and self-isolate for a long period of time. These leads to psychological outcomes such as depression, post-traumatic stress symptoms, panic, confusion, anger, fear, and substance misuse and develops Sedentary Death Syndrome and reduce individuals` functional ability. Increased physical activity levels and fitness help alleviate or relieve Covid-19 associated health problems such as depression, anxiety and stress (mental health) and at this time if an individual follows a physically active lifestyle or participate regularly in home based physical activity, it has been found to be an effective way of improving fitness and overall health of individual. The effect of regular home based exercise training has a significant positive effect on overall health of individuals. Mental and physical well-being are negatively affected by sedentary habits and positively affected by active lifestyle.